A Case of Imatinib Induced Nephrotic Syndrome in a Child with Chronic Myeloid Leukaemia - Mahmuda, Mumtahena; Chowdhury, Tanzila Tabib; Quader, Mohammed Maruf ul; Karim, AKM Rezaul; Nandy, Joydip; Khan, Md Naoshad (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background:Tyrosin kinase inhibitors (TKI) are used as a targeted therapy for the treatment of chronic myeloid leukaemia and Philadelphia chromosome positive acute lymphoblastic leukaemia. Increasing use of TKI has been associated with hypertension, proteinuria and acute kidney injury. There are only afew reports of adults with TK -inhibitor associated nephrotic syndrome.But TK inhibitor associated Nephrotic syndrome is very rare in paediatric age group. Case:A -6- year old boy presented with fever, anaemia, splenomegaly, leucocytosis and finally diagnosed as accelerated phase of chronic myeloid leukaemia (CML) by bone marrow study.He achieved clinical and haematological remission with Imatinib. But developed generalized oedema and was found to have massive proteinuria and microscopic haematuria after three and half months. Renal biopsy revealed focal segmental glomerulosclerosis. Imatinib along with Prednisolone, 60 mg/m2/ day was added to treat nephrotic syndrome. Imatinib discontinued as the patient did not achieve complete remission. After one week of Imatinib withdrawal and five weeks of daily prednisolone the boy attained complete remission of nephrotic syndrome. Conclusion:Tyrosine Kinase inhibitors are important therapies in paediatric cancer and their use is expanding. Timely recognition of renal adverse effectsfor TK inhibitors can aid in the proper management of cancer patients. J Bangladesh Coll Phys Surg 2023; 41: 170-172